The Consequences of Divorce for Financial Living Standards in Later Life - Stanton, D; De Vaus, D; Qu, L; Gray, M (My University, 2007)
As the first generation that experienced high rates of divorce reaches retirement age, the number of older Australians who have experienced divorce at some point in their lives will increase dramatically in coming decades. There is very little empirical evidence in Australia on the financial consequences of divorce for older people. This report begins to fill this gap by providing some of the first estimates of the financial consequences of divorce for Australians aged 55 to 74 years. Using data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey, it was found that, on average, having been divorced had negative consequences for income in older age for both men and women. However, the negative financial impacts of divorce were substantially reduced by remarriage. For some measures of financial circumstances, those who had remarried following divorce were very similar to the married and never-divorced. Older divorced single Australians were much more likely to experience material hardships and to report having a lower level of prosperity than the married and never-divorced. The divorced and single were more reliant on the public pension than those who had not divorced. This will have important implications for the financing of retirement incomes in Australia in coming decades and the extent to which the taxpayer will have to bear the costs of providing for retirement incomes.
Australian Institute of Family Studies Research Paper
Keywords: Finance; Relationships; Relationships -- Divorce; https://melbourneinstitute.unimelb.edu.au/hilda; Health and wellbeing; Income, wealth and finances; Health; Income, wealth and finances